Quercetin 7-rhamnoside protects against alpha-naphthylisothiocyanate (ANIT)-induced in cholestatic hepatitis rats by improving biliary excretion and inhibiting inflammatory responses - Jin, Hong-Liu; Liu, Xiao-Jia; Feng, Xiao-Ying; Zhu, Wen-Ting; Feng, Sen-Ling; Cao, Li-Ping; Yuan, Zhong-Wen (Frontiers in Pharmacology, 2023)
Objective: To explore the pharmacological effects and molecular mechanism of quercetin 7-rhamnoside (Q7R) in the treatment of cholestatic hepatitis induced by alpha-naphthylisothiocyanate (ANIT). Methods: ANIT-induced cholestatic hepatitis rat model was used to investigate the hepatoprotective effects of three different doses of Q7R (1.25 mg/kg; 2.5 mg/kg; 5 mg/kg). Serum biochemical indices were detected using commercial kits. H&E and masson staining were used to observe hepatic tissue damage and collagen deposition in hepatocytes. The metabolism of bile acid-related substances was detected via HPLC-MS/MS by 5-(diisopropylamino) amylamine (DIAAA) derivative method. Hepatocyte injury, cholestasis, and inflammation were detected at the mRNA and protein levels using reverse transcription-polymerase chain reaction (RT-PCR) and western blotting, respectively. Results: Q7R can decrease the level of CYP7A1, and increase FXR, CYP27A1 so then improving abnormal bile acid secretion. Furthermore, Q7R can also ameliorating inflammation by reduce TNF-α, IL-1β, PTGS1, PTGS2, NCOA2, NF-κB level. Therefore, Q7R had an effective therapeutic effect on ANIT-induced cholestatic hepatitis, improving abnormal bile acid secretion, and inhibiting inflammatory responses. Conclusion: The results demonstrated that Q7R treat cholestatic hepatitis by regulating bile acid secretion and alleviating inflammation.